Epigenetic Regulation of Nanog by MiR‐302 Cluster‐MBD2 Completes Induced Pluripotent Stem Cell Reprogramming123. (20th March 2013) - Lee, Man Ryul; Prasain, Nutan; Chae, Hee‐Don; Kim, Young‐June; Mantel, Charlie; Yoder, Mervin C.; Broxmeyer, Hal E.
Abstract While most somatic cells undergoing induced pluripotent stem (iPS) cell reprogramming with Yamanaka factors accumulate at stable partially reprogrammed stages, the molecular mechanisms required to achieve full reprogramming are unknown. MicroRNAs (miRNAs) fine‐tune mRNA translation and are implicated in reprogramming, but miRNA functional targets critical for complete iPS cell reprogramming remain elusive. We identified methyl‐DNA binding domain protein 2 (MBD2) as an epigenetic suppressor, blocking full reprogramming of somatic to iPS cells through direct binding to NANOG promoter elements preventing transcriptional activation. When we overexpressed miR‐302 cluster we observed a significant increase in conversion of partial to fully reprogrammed iPS cells by suppressing MBD2 expression, thereby increasing NANOG expression. Thus, expression of exogenous miR‐302 cluster (without miR‐367) is efficient in attaining a fully reprogrammed iPS state in partially reprogrammed cells by relieving MBD2‐mediated inhibition of NANOG expression. Our studies provide a direct molecular mechanism involved in generating complete human iPS cell reprogramming to study disease pathogenesis, drug screening, and for potential cell‐based therapies. STEM CELLS2013;31:666–681